1989
DOI: 10.1139/b89-238
|View full text |Cite
|
Sign up to set email alerts
|

The impact of duration of drainage on the seed banks of northern prairie wetlands

Abstract: To determine the potential role of seed banks in the restoration of drained wetlands, the seed banks of 30 extant and 52 drained and cultivated prairie potholes were sampled in Iowa, Minnesota, and North Dakota; the potholes had been drained between 5 and 70 years ago. The midsummer vegetation of most of these potholes was also sampled. The number of species in the seed bank of a pothole declined from a mean of 12.3 in extant potholes to 7.5, 5.4, 5.0, 7.4, 3.2, and 2.1 in potholes drained up to 5, 10, 20, 30,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 0 publications
3
56
0
Order By: Relevance
“…Other studies (Wienhold and van der Valk 1989, Hemesath and Dinsmore 1993, Gatatowitsch and van der Valk 1994 have shown that revegetation varies with duration of drainage, past herbicide use and cropping system, effectiveness of drainage, and isolation; these factors should then be considered when selecting restoration sites. Number of breeding bird species and percent vegetation cover increased with wetland age, so efforts should be made to promote long-term restorations through conservation easements or purchase of basins.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Other studies (Wienhold and van der Valk 1989, Hemesath and Dinsmore 1993, Gatatowitsch and van der Valk 1994 have shown that revegetation varies with duration of drainage, past herbicide use and cropping system, effectiveness of drainage, and isolation; these factors should then be considered when selecting restoration sites. Number of breeding bird species and percent vegetation cover increased with wetland age, so efforts should be made to promote long-term restorations through conservation easements or purchase of basins.…”
Section: Management Implicationsmentioning
confidence: 99%
“…The landscape is characterized by hummocky terrain, where wetlands and ponds occupy the ubiquitous depressions (Winter, 1989;van der Kamp and Hayashi, 2009). The region supports a diverse community of wildlife species and major agricultural industry that are highly sensitive to the hydrological conditions (Wienhold and van der Valk, 1989). Hydrological processes in the region are complex and unusual, characterized by closed basins isolated from any regional drainage network, with drainage via a spill and fill sequence into terminal ponds (Shook and Pomeroy, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Little effort, however, has been placed on active revegetation; the assumption generally has been that the native species will recolonize rapidly from remnant seed banks or from seed source wetlands in the landscape (Galatowitsch and van der Valk, 1996c). Seed banks of sedge meadow species, however, are usually depleted because of the often lengthy period of wetland drainage (sometimes 50-100 years) prior to most restorations (Wienhold and van der Valk, 1989). In addition, while some species recolonize quickly from wetlands in the landscape, the characteristic Carex species, that are dominants of natural wetlands in this area, are noticeably absent (Galatowitsch and van der Valk, 1996b,c;Mulhouse and Galatowitsch, 2003).…”
Section: Introductionmentioning
confidence: 99%